Role of Stretching Exerciseon Low Back Pain (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To compare the effectiveness of stretching exercises and diclofenac 50 mg twice daily with diclofenac only in same dosefor the treatment of low back pain.Study Design: Randomize control trial.Place and Duration of Study: The study was conducted in the department of General & Orthopedic Surgery, Foundation University Medical College and Fauji Foundation Hospital Rawalpindi from 1stJanuary 2010 to 31st March2010.Results: Study was conducted on 180 male patients. Age ranges between 20 to 40 years.56.7 % patient has a sedentary life style. Average weight was69.46 kg& average height of 167.30 cm. Plain radiographs of lumbosacral spine reviewed by radiologist to exclude any bony lesion. Base line pain score was marked by the patients themselves from 1 to 10.Patients were divided into two groups. Group 1was treated with diclofenac 50 mg twice daily and muscle stretching exercise. Group 2 was managed only with diclofenac50 mg twice daily. After 7 days, patients in group 1 mark themselves on average of 4.26 on pain scoring chart. While patients in group 2 mark them on 6.26on the same scale. Difference of more than 20 % or 2 on pain scale was considered to be satisfactory. It was concluded that the outcome of patients who managed with physiotherapy in addition to pharmacological agents was much better as compare to medicines alone.Conclusion: While treating the patients of low back pain after base line investigations & excluding all the possible organic lesions, it is recommended to advice muscle stretching exercise as a routine part of treatment. It will not only increase the level of satisfaction of patients but also decrease the duration of pain as well as quick rehabilitation to normal life.
Keywords: Backache, piriformis stretch, side roll stretch & cat back.